2004
DOI: 10.1108/09556220410520414
|View full text |Cite
|
Sign up to set email alerts
|

Processing and quality of cashmere tops for ultrafine wool worsted blend fabrics

Abstract: This study has focussed on three main areas. First, an evaluation of the physical attributes of cashmere tops available to commercial spinners; second, the influence of processing variables on the efficiency of producing cashmere tops from raw Australian cashmere; and third, the influence of design of cashmere ultrafine wool blends on the fibre curvature of tops. Testing the physical attributes of cashmere tops from traditional and new sources of supply, was followed by statistical analyses based on factors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 5 publications
0
20
1
Order By: Relevance
“…The dehairing and combing of the cashmere and wool, top making and spinning were carried out as described previously (McGregor & Postle, 2004. Briefly, the finisher gilling of blended tops used a NSC GV11 Vertical Finisher Gillbox (N. Schlumger et Cie, Guebwiller, France).…”
Section: Spinning and Knittingmentioning
confidence: 99%
“…The dehairing and combing of the cashmere and wool, top making and spinning were carried out as described previously (McGregor & Postle, 2004. Briefly, the finisher gilling of blended tops used a NSC GV11 Vertical Finisher Gillbox (N. Schlumger et Cie, Guebwiller, France).…”
Section: Spinning and Knittingmentioning
confidence: 99%
“…The dehairing and combing of the cashmere and wool, top making and spinning were carried out as described previously (McGregor & Postle, 2004, 2007. Briefly, the finisher gilling of blended tops used a NSC GV11 Vertical Finisher Gillbox (N.Schlumger et Cie, Guebwiller, France).…”
Section: Spinning Knitting and Finishingmentioning
confidence: 99%
“…Until recently, there was little published literature on the effects of wool fibre crimp (curvature) on the properties of knitwear. Recently, the factors affecting the yarn attributes and knitted fabric quality, low-load compressional behaviour and bending properties of yarns and fabrics made from raw superfine merino wools of MFD 17 μm, but differing in fibre curvature and of blends of those wools with cashmere, were investigated in replicated experiments (McGregor & Postle, 2004, 2007, 2008. It was demonstrated that single jersey knitted fabrics made from high fibre curvature wool compared with those made from low fibre curvature wool differ in many fabric properties including: compressibility, suppleness, air permeability, fabric thickness, mass per unit area, spirality, hygral expansion and dimensional stability during laundering.…”
Section: Introductionmentioning
confidence: 99%
“…World cashmeres are judged against the industry standard of Chinese white, that accounts for about half of all cashmere produced in the world. The Chinese National Standard has set the upper limit for the mean fibre diameter (MFD) of cashmere at 16.0 µm (+0.5); the trade organisations of the United States, Europe and Japan have set higher diameter thresholds of up to 19 µm (Cashmere and Camel Hair Manufacturers Institute, 2009;Phan and Wortmann, 2000) although some processed cashmere tops have a fibre diameter of 19 to 20 μm (McGregor and Postle, 2004). In addition to fibre diameter, cashmere buyers also have tight specifications for quality based on the diameter distribution of fibres in the fleece, degree of crimp, colour and lustre.…”
Section: Introductionmentioning
confidence: 99%